Nutritional aspects of enhanced recovery after esophagectomy with gastric conduit reconstruction. Issue 5 (2nd October 2017) - Kingma, B. Feike; Steenhagen, Elles; Ruurda, Jelle P.; van Hillegersberg, Richard
Abstract : Enhanced Recovery After Surgery (ERAS) aims to accelerate recovery by a set of multimodality management strategies. For esophagectomy, several nutritional elements of ERAS can be safely introduced and are advised in routine practice, including preadmission counseling to screen and treat for potential malnutrition, shortened preoperative fasting, and carbohydrate loading. However, the timing of oral intake and the use of routine nasogastric decompression remain matter of debate after esophagectomy. Furthermore, more research is needed on future developments such as perioperative immunonutrition.